From grantmaker to leader : (John Wiley, 2003)
The individual and family-based philanthropic organizations of the early twentieth century might hardly recognize their present-day corporate and institutional successors. The fundamental nature of foundations has changed on a revolutionary scale, forever altering the role that foundations play in society. From Grantmaker to Leader: Emerging Strategies for 21st Century Foundations appraises these shifting dynamics, putting forth powerful strategies for leading philanthropies into the future.